Post-exertional malaise in daily life and experimental exercise models in patients with myalgic encephalomyelitis/chronic fatigue syndrome - Vøllestad, Nina K.; Mengshoel, Anne Marit (Frontiers in Physiology, 2023)
Post-exertional malaise (PEM) is commonly recognized as a hallmark of myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) and is often used as one of several criteria for diagnosing ME/CFS. In this perspective paper we want to reflect on how PEM is understood, assessed, and evaluated in scientific literature, and to identify topics to be addressed in future research. Studies show that patients use a wide variety of words and concepts to label their experience of PEM in everyday life, and they report physical or mental exertions as triggers of PEM. They also report that PEM may have an immediate or delayed onset and may last from a few days to several months. When standardized exercise tests are used to trigger PEM experimentally, the exacerbation of symptoms has a more immediate onset but still shows a wide variability in duration. There are indications of altered muscular metabolism and autonomic nervous responses if exercise is repeated on successive days in patients with ME/CFS. The decreased muscular capacity appears to be maintained over several days following such controlled exercise bouts. These responses may correspond to patients' experiences of increased exertion. Based on this background we argue that there is a need to look more closely into the processes occurring in the restitution period following exercise, as PEM reaches the peak in this phase.